Decreased Serum Brain-Derived Neurotrophic Factor in Poststroke Depression: A Systematic Review and Meta-Analysis - Zhang, Chunhui; Wang, Xuefang; Zhu, Qinghua; Mei, Yongxia; Zhang, Zhenxiang; Xu, Hui (Frontiers in Psychiatry, 2022)
Backgrounds: There were conflicting results of comparison of brain-derived neurotrophic factor (BDNF) levels between post-stroke depression (PSD) patients and stroke patients with no PSD among previous studies. Thus, we conducted this systemic review and meta-analysis to explore the alteration of serum BDNF level in PSD. Methods: The present study included articles published before December 2021 and searched in Web of Science, PubMed databases. STATA 12.0 software was used to compute standard mean difference (SMD) and 95% confidence interval (CI) regarding comparison of serum BDNF in PSD and stroke patients with no PSD. Results: We collected mean value and standard deviation (SD) of serum BDNF in PSD and stroke patients with no PSD from 6 studies (PSD: n = 268, stroke patients with no PSD: n = 425). The present meta-analysis showed decreased serum BDNF level in PSD patients, compared to stroke patients with no PSD with a random effects model [mean value of BDNF level (PSD vs. stroke patients with no PSD): 14.106 vs. 17.995 ng/mL; SMD = -1.578; 95%CI: -2.820, -0.337; I2 = 97.8%, p value for Q test < 0.001]. Conclusions: BDNF may work as a potential biomarker to predict the risk of PSD among stroke survivors. More large-sample clinical trials exploring the alteration of serum BDNF level in PSD among stroke patients are needed to be conducted to verify this result.